Risk & Return Analysis Of Selected Mutual Funds In India - SUDHA, K. NAGA; PARDHASARADHI, S. (The journal of contemporary issues in business and government, 2021)
Sector funds are industry specific funds which invest money in a particular sector of economy such as banking, healthcare, real estate, technology, transportation, etc. These funds provide diversification within a particular sector. They provide stable returns than equity shares. Therefore, investing in sector fund is less risky than that in equity shares. But there returns ability is more volatile than diversified equity mutual funds. The present study is based on analyzing the performance of some selected Indian sector fund schemes in terms of risk and return. In this paper Compound Annualized return, Standard Deviation, Beta, Alpha and R-Squared are determined for last five-year period.